2011
DOI: 10.1142/s1793525311000490
|View full text |Cite
|
Sign up to set email alerts
|

Topology of Random Right Angled Artin Groups

Abstract: Abstract. In this paper we study topological invariants of a class of random groups. Namely, we study right angled Artin groups associated to random graphs and investigate their Betti numbers, cohomological dimension and topological complexity. The latter is a numerical homotopy invariant reflecting complexity of motion planning algorithms in robotics. We show that the topological complexity of a random right angled Artin group assumes, with probability tending to one, at most three values, when n → ∞. We use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Since right-angled Artin groups are indexed over graphs, it is natural to ask about the properties of random ones. Random right-angled Artin groups were studied by Costa-Farber in [3], and their automorphism groups were specifically studied by Charney-Farber in [2]. Charney and Farber showed that under certain conditions, a random right-angled Artin group almost certainly has a finite outer automorphism group; the results of this paper are a sharpening of their results.…”
Section: Introductionmentioning
confidence: 67%
“…Since right-angled Artin groups are indexed over graphs, it is natural to ask about the properties of random ones. Random right-angled Artin groups were studied by Costa-Farber in [3], and their automorphism groups were specifically studied by Charney-Farber in [2]. Charney and Farber showed that under certain conditions, a random right-angled Artin group almost certainly has a finite outer automorphism group; the results of this paper are a sharpening of their results.…”
Section: Introductionmentioning
confidence: 67%
“…if 1 p.n/ D log n !.n/ n . In [12], Costa and the second author analyze the cohomological dimension and the topological complexity of right-angled Artin groups associated to random graphs.…”
Section: The Automorphism Groups Of Random Right-angled Artin Groupsmentioning
confidence: 99%
“…Random right-angled Artin groups, which were first studied in Costa-Farber [12], represent a different class of random groups. The right-angled Artin group associated to a graph is the group generated by the vertex set of with commutation relations between adjacent vertices.…”
Section: Introductionmentioning
confidence: 99%
“…The groups G(n, p, Γ) were considered previously by Charney-Farber [7]. Somewhat earlier, Costa-Farber [8] had looked at the special case of the random right-angled Artin group A G(n,p) . A formula for the cohomological dimension of A G(n,p) (= 1 + dim X(n, p)) in terms of (n, p) can be found in [8], as well as, a formula for the 'topological complexity' of its classifying space.…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat earlier, Costa-Farber [8] had looked at the special case of the random right-angled Artin group A G(n,p) . A formula for the cohomological dimension of A G(n,p) (= 1 + dim X(n, p)) in terms of (n, p) can be found in [8], as well as, a formula for the 'topological complexity' of its classifying space. It is noted in [7] that if each Γ i is finite, then the graph product G(n, p, Γ) is word hyperbolic if and only if G(n, p) has no empty (induced) 4-cycles; furthermore, it is determined when this condition holds 'with high probability' (w.h.p.…”
Section: Introductionmentioning
confidence: 99%